Incidence, Risk Factors, Management and Outcomes of Amniotic-fluid Embolism: A Population-based Cohort and Nested Case-Control Study. Issue 4 (December 2016) - Fitzpatrick, K.E.; Tuffnell, D.; Kurinczuk, J.J.; Knight, M.
Abstract : (BJOG 2016;123:100–109) Amniotic fluid embolism (AFE) is a rare disorder, but it remains a leading cause of maternal mortality in high-income countries. The typical presentation includes sudden cardiovascular collapse without an obvious etiology, respiratory distress and disseminated intravascular coagulation. Because AFE is a rare condition with its diagnosis being one of exclusion, it is difficult to obtain reliable data about the disease. The goal of this study was to report on the incidence, risk factors, management, and outcomes of AFE based on recent data.